Carbon stocks of trees killed by bark beetles and wildfire in the western United States - Hicke, Jeffrey A; Meddens, Arjan J H; Allen, Craig D; Kolden, Crystal A (Environmental research letters, 2013)
Forests are major components of the carbon cycle, and disturbances are important influences of forest carbon. Our objective was to contribute to the understanding of forest carbon cycling by quantifying the amount of carbon in trees killed by two disturbance types, fires and bark beetles, in the western United States in recent decades. We combined existing spatial data sets of forest biomass, burn severity, and beetle-caused tree mortality to estimate the amount of aboveground and belowground carbon in killed trees across the region. We found that during 1984-2010, fires killed trees that contained 5-11 Tg C year−1 and during 1997-2010, beetles killed trees that contained 2-24 Tg C year−1, with more trees killed since 2000 than in earlier periods. Over their periods of record, amounts of carbon in trees killed by fires and by beetle outbreaks were similar, and together these disturbances killed trees representing 9% of the total tree carbon in western forests, a similar amount to harvesting. Fires killed more trees in lower-elevation forest types such as Douglas-fir than higher-elevation forest types, whereas bark beetle outbreaks also killed trees in higher-elevation forest types such as lodgepole pine and Engelmann spruce. Over 15% of the carbon in lodgepole pine and spruce/fir forest types was in trees killed by beetle outbreaks; other forest types had 5-10% of the carbon in killed trees. Our results document the importance of these natural disturbances in the carbon budget of the western United States.